Enhanced impact tolerant core reinforced space shielding - Stokes, Sean; Bayandor, Javid (International journal of impact engineering, 2025)
•Spacecraft shielding performance is benchmarked using traditional space shielding.•Advanced space shield using honeycomb structure is simulated.•Channeling effect was observed for the honeycomb structure.•Standard honeycomb structure performs worse than traditional shielding.•Honeycomb orientation is modified preventing debris channeling.•Novel honeycomb implementation improves shielding performance significantly. The threat of orbital debris to space structures is well understood with efforts being made to develop superior shielding for objects operating in low Earth orbit. In traditional Whipple shield designs, the area between the front bumper and rear pressure wall, termed the stand-off distance, is left empty. One of the more recent discussions in shield design has been the utilization of a honeycomb sandwich core design. In this design an initial thin bumper plate is used to fragment the projectile, followed by a honeycomb design which is implemented to further slowdown the resulting fragments in the stand-off region. By using this implementation, the rear pressure wall is theoretically subject to less damage as a result of the impact, due to the addition of the honeycomb core. It is often argued that the addition of a honeycomb core within the Whipple shield induces a channeling behavior of the projectile, where the sharp edges of the honeycomb split the projectile, and the fragments generated are unable to escape the individual honeycomb core that it is propelled into. It is theorized that this channeling effect causes more damage than an impact where no honeycomb is present. This channeling effect induces a large amount of the mass of the projectile to impact the backplate over a much smaller area. As a result, the damage to the backplate is far more localized and of a higher intensity. In this paper the efficacy of this theory has been studied through an analytical approach, where Whipple shields with the honeycomb and standard 2-plate designs are subjected to hypervelocity impacts of orbital debris. [Display omitted]